Compensation for air transport accidents - محمد أشرف شيخموس شيخو (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Compensation is the effect of liability, which means, the penalty for breach of an obligation. When the liability of the air carrier is realized, the damage is incurred in the event of physical damage to the passenger (safety obligation), loss, damage or loss of goods or baggage Registered) and the delay in the implementation of the air transport contract. Compensation is estimated to the extent of damage according to the general rules of the Civil Code, but in the field of air transport the legislator has departed from this rule, having set a maximum compensation for the carrier responsible, In charging the carrier with liability for the entire damage (unlimited liability), the carrier may lead to the abyss of bankruptcy, thus depriving the carrier of its work in this important economic facility, while the international legislator did not neglect the passenger or shipper, as did not allow the derogation from the ceiling set by International agreements, so as to find a balance between the parties to the contract of carriage. The international legislator has endeavored to maintain the limited liability of the air carrier as long as it is good faith, but when it becomes ill-intentioned it becomes liable for the full damage and does not benefit from limited liability, and if the parties agree that compensation for the full damage is possible, because it does not contravene the public order.